2021
DOI: 10.1101/2021.02.01.21250853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In-Hospital Continuation With Angiotensin Receptor Blockers Is Associated With a Lower Mortality Rate Than Continuation With Angiotensin Converting Enzyme Inhibitors in Covid-19 Patients: A Retrospective Cohort Study

Abstract: BackgroundSeveral studies have reported a reduced risk of death associated with the inpatient use of angiotensin receptor blockers (ARBs) and angiotensin converting enzyme inhibitors (ACEIs) in COVID-19 patients, but have been criticized for incurring in several types of bias. Also, most studies have pooled ACEIs and ARBs as if they were a unique group, overlooking their pharmacological differences. We aimed to assess whether the in-hospital continuation of ARBs and ACEIs, in regular users of these drugs, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…There are few studies designed to compare use of ARBs-only with ACEi-only on pneumonia risk. In our direct comparison of ACEi-only and ARBs-only users who were well-matched for baseline characteristics, we found ARBs were superior to ACEi in reducing pneumonia events, which are consistent with some studies [25]. Both ARB and ACEi effectively block RAS, but only ARB selectively blocks the AT1-receptor and increases expression of ACE2 [26,27].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There are few studies designed to compare use of ARBs-only with ACEi-only on pneumonia risk. In our direct comparison of ACEi-only and ARBs-only users who were well-matched for baseline characteristics, we found ARBs were superior to ACEi in reducing pneumonia events, which are consistent with some studies [25]. Both ARB and ACEi effectively block RAS, but only ARB selectively blocks the AT1-receptor and increases expression of ACE2 [26,27].…”
Section: Discussionsupporting
confidence: 89%
“…Given the high RAS activity in patients with diabetes, appropriate use of RASi is critical to protect the organs from the deleterious effects of Ang-II [25][26][27]. While both clinical trials and real-world evidence (RWE) had con rmed the bene ts of RASi on cardiovascular-renal outcomes [28,29], similar data on pneumonia as a major cause of morbidity and mortality in diabetes remain scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty two of these studies have already been completed. Some of the studies suggested reconsideration of ARBs in the treatment of COVID-19 patients and highlight the potential beneficial role of ARBs to improve the clinical outcomes of COVID-19 patients by controlling the RAAS (Renin-Angiotensin-Aldosterone System) dysfunction. , Other studies confirm safety of the ARBs treatment in COVID-19 patients this type of uncertainty suggesting that ARBs may worsen the condition of patients with COVID-19 arose at the beginning of the pandemic and has been refuted. In addition to clinical trials, molecular docking studies have also been conducted to demonstrate the potential of ARBs to inhibit the COVID-19 main proteasethe best results were obtained for fimasartan and candesartan …”
Section: Introductionmentioning
confidence: 99%
“…A recent preprint of a retrospective cohort study suggested higher survival rates for in-hospital high-risk COVID-19 patients with the use of ARBs than ACEIs ( de Abajo et al, 2021 ). Another retrospective cohort study in Wuhan suggested the beneficial role of ACEI/ARBs over calcium channel blockers in COVID-19 patients with hypertension ( Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%